Competitiveness Factors and MSME Performance: Insights from Jambi Province - Tona Aurora Lubis; Firmansyah, Firmansyah; Mukhzarudfa, Mukhzarudfa; Utama, Ahmad Nur Budi; Sari, Novita; Ningsih, Maryati (Cita konsultindo, 2025)
This study aims to analyze the impact of competitiveness factors on MSME performance in Jambi Province. The research focuses on four key competitiveness factors: financial capabilities, entrepreneurial skills, government policies, and technological advancements. Utilizing a quantitative approach, data were collected from 100 MSMEs through structured questionnaires. The analysis was conducted using Partial Least Squares (PLS) through Smart PLS 3 software. The findings indicate that entrepreneurial skills are the most significant factor influencing MSME performance, with profit growth identified as a key performance indicator. These results suggest that enhancing entrepreneurial capabilities and leveraging regional strengths can improve MSME competitiveness and sustainability in both local and global markets.